Embryonic toxicology evaluation of novel Cissus quadrangularis, bioceramics and tendon extracellular matrix incorporated scaffolds for periodontal bone regeneration using zebrafish model - S. Balaji Ganesh; Manoj Aravindan; Gurumoorthy Kaarthikeyan; Taniya Mary Martin; Meenakshi Sundaram Kishore Kumar; S. Chitra (Journal of Oral Biology and Craniofacial Research)
Introduction: The development of novel scaffold incorporating Cissus quadrangularis extract, bioceramics and tendon extracellular matrix (ECM) for periodontal bone regeneration necessitates a thorough assessment of their embryotoxicity to ensure biocompatibility and safety. This study evaluates the embryonic toxicology of these innovative scaffold using the zebrafish model, which provides a rapid transparent and highly sensitive system for assessing development toxicity. Materials and methods: Zebrafish embryos were exposed to scaffold containing Cissus quadrangularis extract (80 % ethanol), bioceramics, and tendon extracellular. Briefly, the scaffold immerged in the E3 medium for 48h and the extract (10, 50 and 100μl/ml) was evaluated against developing embryos for different developmental anomalies such as survival, malformation, heartbeat and the expression of RunX2 and Bmp2 genes. Results: The results showed that the SEM analysis revealed that the membrane was rough in nature. FTIR analysis confirmed the presence of hydroxylate groups, collagen and hydroxyapatite in the synthesized membrane. Meanwhile, the scaffold did not show any of the developmental defects such as hatchability inhibition and neural toxicity. The mortality was comparable to negative control. Further, the study revealed that the scaffold induced the osteogenic potential by elevating the RunX2 and Bmp2 expression. Conclusion: This study highlighted the inclusion of C. quadrangularis extract could be a beneficial for enhancing periodontal bone regeneration. Further, this also revealed that the extract did not impede the normal tissue development or regeneration using zebrafish embryo as a model.